Spinal Region Segmentation for Intervertebral Distance of X-Ray Images Using Spectral Analysis (Medico Legal Update, 2021)
Physics plays a vital role in cultivating the knowledge of natural sciences and establishing the foundation oflogistic and scientific method. The application of physics to medical sciences has been developed in practicefor centuries. X-Ray, CT scan and MRI images of the spine provide a practical approach for detectingand assessing vertebral abnormalities. For accurate vertebra detection number of features of an image canbe extracted and meaningful information can be obtain from low level information in the image usingsegmentation. In this paper a method is proposed for making treatment of spinal traction efficient and feasibleby using image processing algorithm based on the data obtained from the survey and images of the patients.